Alien species of Ipomoea in Greece, Türkiye and Iran: distribution, impacts and management - Sima Sohrabi; Ayşe Yazlık; Ioannis Bazos; Javid Gherekhloo; Vaya Kati; Yasin Emre Kitiş; Margarita Arianoutsou; Alessandra Kortz; Petr Pyšek (NeoBiota)
New introductions of alien Ipomoea species and their negative impacts have increased in Greece, Türkiye, and Iran. However, little is known about their current status, distribution, impacts, and management. Here, we provide a detailed overview of Ipomoea species in these countries and discuss the current and proposed management options for restoring invaded plant communities. We report on four alien Ipomoea species in Greece (three naturalized and one casual), 10 in Türkiye (eight naturalized and two casual), and 11 in Iran (eight naturalized of which two are invasive and three casual). Their most significant negative impact was detected in agricultural areas, especially in spring crops like soybean, cotton, and maize, with I. hederacea, I. purpurea, and I. triloba being the most troublesome weeds. Native plants are mainly threatened by I. indica, I. leucantha, and I. triloba. The management of Ipomoea species differs according to the habitats invaded; in agricultural areas, the management is more dependent on the host crop and the available registered herbicides, whereas in areas with natural habitats, other management options such as mechanical and biological measures are more appropriate. The information from this work will be useful for the early detection of Ipomoea species in countries neighboring the already invaded ones.